Protecting Intellectual Property In The Digital Age With A Law - Irsan Rahman; Sinintha Yuliansih Sibarani; Sandi Aprianto; Arman Paramansyah; Ayu Citra Santyaningtyas (Journal of Research in Social Science and Humanities, 2024)
Life has changed with the development of science and technology. One technology that has a significant impact is the technology of the Internet world, the Internet introduces people to the digital world. Of course, this development also affects the law, especially copyright law. Copyrighted works that were still in a traditional form can now be converted to a digital form or digital copyrighted works can be created. In this case, copyright law, which previously protected traditional forms of copyrighted works, must evolve to include the protection of digital copyrighted works, one of which is through cooperation with technology. This research is a normative study with a focus on how copyright law, which previously protected traditional forms of copyright, must evolve to include protection of digital copyrights, one of which is through cooperation with technology. This research is a normative research with a qualitative approach that is descriptive. As technology allows the conversion of copyrighted works into digital forms, there are advantages such as the easy distribution/notification of copyrighted works, but also the ease of infringement. In view of these developments, the WIPO has issued two international treaties known as the WIPO Internet Treaties. These treaties have been adopted by several countries. Indonesia in its positive copyright law has implemented the protection of digital copyrighted works in its articles. Our copyright law needs to be further enriched to protect digital copyrighted works as suggested by the author in this study